PENGARUH PERUBAHAN STANDAR AKUNTANSI KEUANGAN (SAK) TERHADAP EFISIENSI BANK PERKREDITAN RAKYAT (BPR) DENGAN PENDEKATAN DATA ENVELOPMENT ANALYSIS (DEA) - Suprihadi, Suprihadi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2011)
The study was conducted to examine the effect of changes in Financial Accounting Standards (SAK) business Rural Bank (BPR), with the enactment of the Financial Accounting Standards Un Accountability Public-entity-(SAK-ETAP) and the Rural Bank Accounting Guidelines (PA-BPR), to BPR efficiency. SAK changes may result in changes to the financial performance of business efficiencies, especially BPR. Efficiency is one of the performance parameters which theoretically can be used as a basis for determining the performance of the bank. Non-parametric approach to Data-Envelopment Analysis (DEA), used as a tool for evaluating the efficiency of BPR, with input variables (cash, placements with other banks, fixed assets, other assets, third party financing, interest income, interest expense, expense fees and expenses operational) and the output variable (that is given credit, loans received, and net income). Analysis of the influence of changes in accounting standards on the efficiency of BPR, performed using Analysis of Variance analysis tools-(ANOVA) and regression bootstrap method. The results showed that, for BPR in East Java which has total assets of Rp. 10 (ten) million, changes in accounting standards had no effect on the efficiency of BPR. The condition is caused by, changes in financial accounting standards, fundamentally, is the reclassification and changes in the presentation of accounts in the financial statements BPR. Key words: Financial Accounting Standards, Efficiency, BPR, DEA